Major Depressive Disorder and Measures of Cellular Aging: An Integrative Review - Patricia Anne Kinser; Debra E. Lyon (Nursing Research and Practice)
Major depressive disorder (MDD) affects millions of individuals and causes significant suffering worldwide. It has been speculated that MDD is associated with accelerated aging-related biological and functional decline. To examine the accelerated aging hypothesis, one of the biomarkers under study is leukocyte telomeres, and specifically the measure of telomere length and telomerase activity. This review integrates findings from eleven human studies which evaluated telomere length and telomerase activity, in order to synthesize the state of the current science and to inform the development of new knowledge and enhance nursing research of depression using appropriate biobehavioral measures. Although preliminary, the findings from this integrated review suggest that there is evidence to support a conceptualization of depression as a stress-related condition in which telomeres shorten over time in relation to cumulative exposure to the chronic stress of depression. For the purposes of testing in future nursing research, visual representations of the theoretical connection between stress vulnerabilities, depression, and health outcomes and key moderators and mediators involved in this conceptualization are provided. The findings from this review and the conceptual framework provided may be a useful step towards advancing therapeutic nursing interventions for this debilitating chronic condition.